A creative analysis of the role of practice development facilitators in a critical care environment - Tanya Heyns; Yvonne Botma; Gisela van Rensburg (AOSIS, 2017)
Practice development focuses on methods to address the quality of care and advance healthcare practices. The role of practice development facilitators to address challenges of delivering evidence-based person-centred care in the critical care environment was determined by using a nominal group technique. Eleven participants from public and private healthcare services reached consensus on seven clusters: theory-practice application, facilitation of learning, increasing collaboration, effective communication, facilitation of change, time management and role modelling. The clusters were visually represented as a hot air balloon. Competence as facilitators is of vital importance to ensure knowledge translation with the aim to improve quality.